Respuesta :

Answer:

The answer to your question is: L = (P - 2W) / 2

Step-by-step explanation:

                      Equation              P = 2L + 2W            solve for L

                                                  2L + 2W = P          

                                                  2L = P - 2W              pass 2W to the right side

                                                                                    subtracting

                                                  L = (P - 2W) / 2        pass 2 to the right side

                                                                                   dividing

                             

                               

Answer:

The answer to your question is: L = (P - 2W) / 2

Step-by-step explanation:

                     Equation              P = 2L + 2W            solve for L

                                                 2L + 2W = P          

                                                 2L = P - 2W              pass 2W to the right side

                                                                                   subtracting

                                                 L = (P - 2W) / 2        pass 2 to the right side

                                                                                  dividing

ACCESS MORE